ANALISIS PENGGUNAAN ”BAHASA DAN STRUKTUR BAHASA DALAM INTERAKSI SOSIAL SEHARI-HARI” - Nora Feretty Anggel Manalu; Selvisari Br Ginting; Puput Adelina Sianturi; Tasya Aflina Silaban (Journal Education and Government Wiyata, 2025)
The analysis of language use and language structure in everyday social interactions is an important study that reveals how language functions within social contexts. This research aims to explore how individuals utilize language in various social situations and how language structure influences meaning and comprehension. Using a qualitative approach, data were collected from everyday conversations, both in-person and through digital media. The analysis results indicate that language use is influenced not only by situational context but also by factors such as culture, identity, and communication goals. These findings provide insights into the dynamics of social interaction and the significance of understanding linguistic nuances in building interpersonal relationships